Editorial: Understanding the role of oscillations, mutual information and synchronization in perception and action - Bahmer, Andreas; Rimmele, Johanna M.; Gupta, Daya Shankar (Frontiers in Computational Neuroscience, 2024)
No abstract as the text is an editorial.